The Incidence of Perioperative Adverse Events in the Very Elderly Undergoing Urogynecologic Surgery. Issue 6 (November 2016) - Unger, Cecile A.; Hickman, Lisa C.; Mitchell-Handley, Blair; Barber, Matthew D.; Ridgeway, Beri
Abstract : Objectives: To determine the incidence of perioperative adverse events in very elderly women (age ≥ 80 years) undergoing urogynecologic procedures and to examine the effect of preoperative functional status/capacity on these outcomes. Methods: This is a retrospective analysis of all women aged 80 years or older who underwent a urogynecologic procedure at a tertiary care specialty practice between 2006 and 2014. Subjects were identified by their Current Procedural Terminology codes and the electronic medical record was queried for demographic and perioperative data. Functional status was recorded using data from the preoperative anesthesia assessment, and included the functional status score (range, 1–4) and a functional capacity evaluation (metabolic equivalents [METs, range, 1 to 8+]). Results: One hundred sixty-four women aged 80 years or older underwent a urogynecologic procedure during the study period. Mean age was 83 years (±3; range, 80–95 years). The median functional status was 2 (1–4) and median functional capacity was 5.5 METs (1.75–8.0). The overall postoperative adverse event rate was 18.3%; the incidence of serious events was 7.8%. Most serious events were associated with preexisting medical conditions. Presence of 3 or more comorbid conditions was associated with a higher risk of postoperative readmission, need for transfusion and deep vein thrombosis/pulmonary embolism. Preoperative functional status and functional capacity were not associated with postoperative adverse events. Patients with METs scores of 4.5 or less were more likely to need home services or a skilled nursing facility (SNF) postoperatively compared with patients with higher scores (28.9% vs 6.7%, P < 0.0001; odds ratio, 4.3; 95% confidence interval, 1.6–11.9). Dementia was also associated with SNF admission (36.3% vs 10%; P = 0.01; odds ratio, 3.6; 95% confidence interval, 1.1–12.8). Conclusions: The incidence of serious postoperative adverse events is low in very elderly patients undergoing urogynecologic procedures. Dementia and poor functional capacity appear to be associated with a higher need for postoperative home services or SNF admission. Abstract : The risk of perioperative serious adverse events in the very elderly undergoing urogynecolgic surgery appears to be low.